Relevance of Husein Muhammad’s Gender Thought in the Existence of Female Judges in District Courts - Shiddiqi, Hasbi Ash; Hasyim, Yanto; Rofikoh, Rofikoh; Amin, Faris El; Ramadhan, Taha (Al Irsyad: Jurnal Studi Islam, 2026)
Female judges in the District Court of Jember Regency face tensions between classical fiqh perspectives and modern judicial practices, including social, structural, and gender-based barriers that limit their participation. This study aims to analyze the relevance of Husein Muhammad’s gender thought and gender-just Islamic interpretations to the existence and role of female judges. Employing a qualitative empirical approach, data were collected through in-depth interviews with a female judge, document analysis, and literature review on gender discourse in Islam and judicial practice. The findings reveal that female judges possess equal authority and responsibility as male judges but continue to encounter social and structural challenges, including domestic burdens and gender stereotypes. Husein Muhammad's perspective, when viewed through the lens of maq??id al-shar?‘ah, offers a robust theological and ethical foundation for gender equality, highlighting the tenets of justice, public benefit (maslahah), and human dignity. This framework supports the idea that women should participate in the judiciary, thus reducing the influence of patriarchal views in legal decisions. The research shows that it's possible to combine modern religious discussions with established legal procedures. Ultimately, incorporating gender-sensitive Islamic thought into judicial practice can foster a more inclusive and fair legal system. The study's importance resides in its provision of a contextual Islamic framework that endorses women's participation and challenges patriarchal interpretations found within traditional fiqh.